Integrated Marketing Communication, Brand Equity, and Perceived Value in Shaping Tourist Loyalty: Evidence from Nusa Penida Tourism - Iswahyu Pranawukir; Rudy Haryanto; Dipa Teruna Awaludin; Rustaniah; Aprih Santoso (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2026)
Nusa Penida in Bali has emerged as a marine tourism destination facing intensifying competition while continuing to attract both domestic and foreign visitors. This competitive environment requires highly integrated marketing communications to reinforce destination brand strength, enhance tourists' perceived value, and stimulate long-term loyalty. This research examines the causal relationships and structural linkages among Integrated Marketing Communication (IMC), Brand Equity, Perceived Value, and Tourist Loyalty using a quantitative framework based on Partial Least Squares–Structural Equation Modeling (PLS-SEM). The study involved 150 respondents who had previously traveled to Nusa Penida and were selected using purposive sampling criteria. Primary data were collected using a structured survey instrument and analyzed using SmartPLS 4. The empirical findings indicate that IMC positively and significantly influences both Brand Equity and Perceived Value. In addition, Brand Equity and Perceived Value serve as mediating mechanisms that amplify IMC's impact on Tourist Loyalty. The structural model evaluation revealed a high R-square for the loyalty construct, demonstrating the model's strong explanatory power for variation in tourist behavior. Overall, the results highlight the critical role of consistent and integrated marketing communication in shaping destination image, increasing perceived value, and cultivating tourist loyalty. From a practical standpoint, the findings emphasize the importance of collaboration among destination authorities, local governments, and tourism stakeholders in developing a robust digital-based marketing communication ecosystem to ensure Nusa Penida’s sustained competitiveness as a world-class marine tourism destination.